Ticks, Ixodes scapularis, Feed Repeatedly on White-Footed Mice despite Strong Inflammatory Response: An Expanding Paradigm for Understanding Tick–Host Interactions - Anderson, Jennifer M.; Moore, Ian N.; Nagata, Bianca M.; Ribeiro, José M. C.; Valenzuela, Jesus G.; Sonenshine, Daniel E. (Frontiers in Immunology, 2017)
Ticks transmit infectious agents including bacteria, viruses and protozoa. However, their transmission may be compromised by host resistance to repeated tick feeding. Increasing host resistance to repeated tick bites is well known in laboratory animals, including intense inflammation at the bite sites. However, it is not known whether this also occurs in wild rodents such as white-footed mice, Peromyscus leucopus and other wildlife, or if it occurs at all. According to the “host immune incompetence” hypothesis, if these wild mice would do not have a strong inflammatory response, they would not reject repeated tick bites by Ixodes scapularis. To test this hypothesis, histopathological studies were done comparing dermal inflammation in P. leucopus versus guinea pigs, Cavia porcellus, repeatedly infested with I. scapularis. In P. leucopus, the immune cell composition was like that seen in laboratory mouse models, with some differences. However, there was a broad sessile lesion with intact dermal architecture, likely enabling the ticks to continue feeding unimpeded. In contrast, in C. porcellus there was a relatively similar mixed cellular profile, but there also was a large, leucocyte-filled cavitary lesion and scab-like hyperkeratotic changes to the epidermal layer, along with itching and apparent pain. Ticks attached to sensitized C. porcellus fed poorly or were dislodged, presumably due to the weakened anchoring of the tick’s mouthparts cemented in the heavily inflamed and disintegrating dermal tissues. This is the first time that the architecture of the skin lesions has been recognized as a major factor in understanding tick-host tolerance versus tick bite rejection. These findings broadly strengthen previous work done on lab animal models but also help explain why I. scapularis can repeatedly parasitize white-footed mice, supporting the “immune evasion theory” but why they cannot repeatedly parasitize other, non-permissive hosts such as guinea pigs.